2012
DOI: 10.1159/000337252
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Calibre, Geometry and Progression of Diabetic Retinopathy in Type 2 Diabetes Mellitus

Abstract: Purpose: To determine whether changes in retinal vascular calibre and geometry are associated with progression of diabetic retinopathy in type 2 diabetes (T2D). Procedures: The retinal vascular calibre and geometry of 30 subjects with more than 20 years of diagnosed T2D with no retinopathy (NR) were compared to 30 subjects that progressed to proliferative diabetic retinopathy (PDR). The images of PDR subjects included in this study were those obtained before the onset of retinopathy. The diameter of retinal ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 102 publications
7
46
0
Order By: Relevance
“…21 Most clinical studies measuring Fd have included patients with type 1 diabetes mellitus, 12,13,22À24 patients with increased levels of HbA1c, 25,26 or examined data from patients with diabetes who developed DR over time. 27À29 In a cross-sectional study, Grauslund et al 12 found an independent correlation between lower Fd and the presence of inactive PDR as well as neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…21 Most clinical studies measuring Fd have included patients with type 1 diabetes mellitus, 12,13,22À24 patients with increased levels of HbA1c, 25,26 or examined data from patients with diabetes who developed DR over time. 27À29 In a cross-sectional study, Grauslund et al 12 found an independent correlation between lower Fd and the presence of inactive PDR as well as neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43] BC was calculated to measure the changes in the total cross-sectional area across the bifurcation. An increased BC represented wider branch vessels, and a decreased branching coefficient indicated narrower branch compared with the trunk vessel.…”
Section: Measurement Of Retinal Vascular Parametersmentioning
confidence: 99%
“…The intra-retinal vasculature lacks autonomic innervation and close-regulation of blood flow through the inner retina is dependent on cell-cell signalling mechanisms(Delaey et al, 2000). Abnormalities of retinal blood flow in diabetic patients were reported by Wagener in the 1930's(Wagener et al, 1934) and as technology for assessing vascular function improved there were further indications that vessel calibre changed during diabetic retinopathy(Ballantyne and Loewenstein, 1943;Skovborg et al, 1969) with some predictive value(Crosby- Nwaobi et al, 2012) . In the 70's, seminal work by Kohner described hemodynamic changes in the diabetic retinal vasculature with a strong assertion that these abnormalities were connected to pathology and could form the basis of an early-stage indicator for diabetic retinopathy progression(Kohner, 1993; Kohner et al, 1975).…”
mentioning
confidence: 96%